Systemic Thinking in Financial Regulation: A Conversation with Professor Steven Schwarcz, Distinguished Visiting Professor, UCL Faculty of Laws - Sriram Kilapakkam; Xueming Wang; Sriram Kilapakkam; Xueming Wang (UCL Journal of Law and Jurisprudence, 2018)
Professor Steven Schwarcz, Stanley A. Star Professor of Law and Business at Duke University, was Distinguished Visiting Professor at the UCL Faculty of Laws between mid-January to mid-May 2018. We invited him to an interview to discuss his extensive scholarship on financial regulation - in particular, relating to how financial regulation can ‘fix’ the problems of financial crises, such as the global financial crisis 2007-9. The interview took place on 28 March 2018 at Bentham House. Professor Schwarcz’s scholarship and thinking spans financial institutions, markets and systems regulation and the importance of incentive-based corporate law and regulation, presenting a rich tapestry of enduring insights for regulatory policy at their most fundamental levels. Professor Schwarcz’s background in engineering and as a practitioner of bankruptcy and international financial law prior to entering academia uniquely positions him to view financial regulation from an alternative and functional perspective to address many of the problems in today’s financial markets. His analysis of legal issues has drawn on cross disciplinary insights from diverse fields such as economics and from the functioning of engineering systems. He has offered many creative and practical suggestions and solutions to addressing systemic risk, which has risen in prominence as a topic for regulatory discussion in the wake of the global financial crisis. He has also written extensively on a whole range of topics including microprudential regulation, bank resolution, shadow banking, ring-fencing, securitisation, restructurings and securities disclosure issues. Professor Schwarcz was engaged on some of these points in the course of the interview. This paper is presented in the format of an interview, but the text is a (non-verbatim) transcription and not a replication of the conversation, as the interview was not recorded. In terms of the interviewers, Sriram is represented by ‘S’, while Xueming is represented by ‘X’. Professor Schwarcz is represented by ‘P’. For full text, please click here